Characterization Of Biomechanical Properties Of Articular Cartilage Across Synovial Joint - Jaafar, Yusra Liyana (2017)
Degradation and loss of articular cartilage in synovial joint has long been recognized as the main source of osteoarthritis (OA). It is generally accepted that the biomechanical properties of articular cartilage seem to be more sensitive to pathological changes of the tissue. Extensive studies of cartilage have been carried out to characterize the biomechanical properties using both experimental and analytical approaches. These properties were then applied in computational models to investigate the biomechanical behavior of the cartilage. However, analytical analysis was developed based on the theory which idealized the geometrical and physical conditions of the cartilage and subchondral bone. Furthermore, previous experimental studies require the cartilage to be isolated which could possibly damage the cartilage. These could be the main reason as the behavior of the cartilage across the synovial joint is yet to be fully understood because it appears that only part of the cartilage in synovial joint were previously being investigated. Therefore, the study aims to develop new approach to integrate the experimental and computational methods which could enable to characterize the elastic modulus and permeability of the cartilage across the synovial joint. Articular cartilage of bovine humeral head was used to perform the indentation test in order to obtain experimental data. The cartilage was measured using profile projector for development of finite element (FE) model. New approach to integrate the experiment data and FE model were developed to examine the cartilage biphasic elastic modulus and permeability. Based on the result, the elastic modulus increased by 150.6% when cartilage thickness was increase more than twice. Meanwhile, opposite trend was seen for permeability, where the permeability decrease as the cartilage became thicker with 118.9% percentage difference. This could indicate that the actual geometry of cartilage includes of cartilage thickness and curvature does effect the biomechanical properties of articular cartilage across synovial joint. These findings will be serving as a guide in enhancing tissue engineering developments for cartilage repair and as an input for computational studies.